A microanalysis of the sophomore and senior translation students' uncertainty management in the process of translation: a complex dynamic approach. Issue 1 (2nd January 2020) - Lavasani, Goharsadat S.; Elahi Shirvan, Majid; Ghanizadeh, Afsaneh
ABSTRACT: Translation as a problem-solving and decision-making process embodies various natural instances of indecisiveness (uncertainty or ambiguity) for finding the best solution as the final translation. In this case study, we aimed to explore English translation students' uncertainty management at sophomore and senior levels in the process of translation at a micro level from a complex dynamic systems theory (CDST) perspective in terms of variability, complexity, and context. A triangulation of data collection including keystroke logging, screen recording, and stimulated recall protocols was used in this study. The results of this study indicated that the translation students' uncertainty management can be regarded as a complex system. First of all, intra-individual change and inter-individual variability were observed in the pattern of the translation students' uncertainty management. Secondly, the translation students experienced intra-level stability in terms of the main dimensions of uncertainty management as well as the loci of translation process. Finally, the influence of the education system on the dynamic patterns of uncertainty management of translation students was tangible and the senior students showed higher level of uncertainty management for resolving uncertainties during translation.